Evidence on the international evolution and convergence of corporate governance regulations - Martynova, Marina; Renneboog, Luc (Journal of Corporate Finance, 2011)
The issue of appropriate corporate governance framework has been a focal point of recent reforms in many countries. This study provides a comprehensive comparative analysis of corporate governance regulatory systems and their evolution since 1990 in 30 European countries and the US. It proposes a methodology to create detailed corporate governance indices which capture the major features of capital market laws in the analyzed countries. The indices indicate how the law in each country addresses various potential agency conflicts between corporate constituencies: namely, between shareholder and managers, between majority and minority shareholders, and between shareholders and bondholders. The analysis of regulatory provisions within the suggested framework enables us to understand better how corporate law works in a particular country and which strategies regulators adopt to achieve their goals. The 15-year time series of constructed indices and large country-coverage also allows us to draw conclusions about the convergence of corporate governance regimes across the countries.